Piwi-like 1 and 4 gene transcript levels are associated with clinicopathological parameters in renal cell carcinomas - Al-Janabi, Omar; Wach, Sven; Nolte, Elke; Weigelt, Katrin; Rau, Tilman; Stoehr, Christine; Legal, Wolfgang; Schick, Stefan; Greither, Thomas; Hartmann, Arndt; Wullich, Bernd; Taubert, Helge (Biochimica et Biophysica Acta - Molecular Basis of Disease, 2014)
Piwi-like gene family members (Piwil 1-4) are considered stem cell-associated genes/proteins. These are expressed predominantly in germline cells, but are re-expressed in different tumors. Piwil 1-4 gene expression has not previously been studied and correlated with clinicopathological parameters in renal cell carcinomas (RCC). The Piwil 1-4 transcript levels were analyzed by quantitative real-time PCR in 73 clear cell RCC (ccRCC) tissues and corresponding normal tissues. The transcript levels of Piwil 1, 2 and 4 were strongly and significantly correlated with each other, in both the tumor tissues and the normal tissues (P<0.001; Spearman's rank test). Piwil 4 gene expression was significantly higher in the ccRCC tissues than that in the corresponding normal renal tissues (P<0.001; Wilcoxon signed-rank test). When the ccRCC patient cohort was divided according to the median Piwil 1-4 expression into low- and high-expression groups and according to age into younger (<=64years) and older patient groups (>64years), the younger patients displayed significantly higher levels of Piwil 1 mRNA in comparison to the older patients (P=0.010; Fisher's exact test). Interestingly, Piwil 1 expression was left-right polarized in the normal tissues but not in the tumor tissues (P=0.004; Fisher's exact test). Altogether, associations were determined between the Piwi-like family member expression levels and clinicopathological parameters of ccRCC, suggesting a potential role for these genes/proteins in ccRCC diagnostics and tumorigenesis as well as in renal tissue embryology.
EVALuna2:6563